(untitled) (Conferencea, 2024)
Antibiotics remain a cornerstone of modern medicine, yet their widespread and often inappropriate use has led to significant challenges, including the emergence of antibiotic resistance and an increased incidence of drug-related side effects. This article explores the principles of rational antibiotic therapy, focusing on optimizing drug selection, dosage, and duration to maximize efficacy while minimizing adverse outcomes. Additionally, we introduce common side effects associated with antibiotics, discussing both pharmacological and clinical management strategies to mitigate these reactions. Importantly, the paper also addresses the growing global concern of antibiotic resistance, emphasizing the need for stringent antimicrobial stewardship programs and the development of novel approaches to prevent resistance. Preventative strategies, such as antibiotic rotation, patient education, and the promotion of infection prevention measures, are also considered. Through a comprehensive understanding of antibiotic therapy, healthcare professionals can improve patient outcomes while curbing the threat of antibiotic resistance.